2019
DOI: 10.1007/s12298-019-00728-7
|View full text |Cite
|
Sign up to set email alerts
|

NaCl induced oxidative stress in legume crops of Indian Thar Desert: an insight in the cytoprotective role of HO1, NO and antioxidants

Abstract: The manuscript highlights the role of antioxidants in alleviation of salinity stress in two principal legume crops Cyamopsis tetragonoloba and Vigna radiata of Indian Thar Desert. The study evaluates correlation between the antioxidants of two cultivars in terms of morphological and physiological alterations. Hydroponically acclimatized seedlings of both the crops were subjected to NaCl stress at different concentrations ranges from 10 to 100 mM. After 96 h, the treated legumes were harvested to analyze the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 56 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…Pretreatment of wheat seedling with glucose activates NR to produce NO under aluminum stress (Sun et al, 2018). It has been reported that endogenous NO production could influence the salinity tolerance of several plants, mostly via stimulation of antioxidant defense mechanisms (Khator et al, 2000;Ali et al, 2017;Gadelha et al, 2017;Klein et al, 2018) and suppression in uptake of toxic ions (Fatma et al, 2016;Gadelha et al, 2017). The UA-mediated endogenous NO production may be partly explained the alleviation of salt stress in rice cultivars in the present study.…”
Section: Potential Mechanism Of Ua-mediated Salt Tolerancesupporting
confidence: 49%
“…Pretreatment of wheat seedling with glucose activates NR to produce NO under aluminum stress (Sun et al, 2018). It has been reported that endogenous NO production could influence the salinity tolerance of several plants, mostly via stimulation of antioxidant defense mechanisms (Khator et al, 2000;Ali et al, 2017;Gadelha et al, 2017;Klein et al, 2018) and suppression in uptake of toxic ions (Fatma et al, 2016;Gadelha et al, 2017). The UA-mediated endogenous NO production may be partly explained the alleviation of salt stress in rice cultivars in the present study.…”
Section: Potential Mechanism Of Ua-mediated Salt Tolerancesupporting
confidence: 49%
“…In the present study, we also demonstrated the lipid peroxidation level under UV-B exposure to analyse the oxidative damage within the cellular membrane. In W. coagulans, UV-B supplementation increased MDA content gradually with UV-B exposure, which is a well-known indicator of membrane damage in plant cells (Khator et al 2020 ). Significant increase in MDA content after 3 h UV-B exposure suggested that UV-B radiation created oxidative damage cannot be counteracted by an antioxidative defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These metalloenzymes are highly conserved and represent the major H 2 O 2 scavenging enzyme [ 5 ]. Moreover, they are regulators of different biological and physiological processes such as growth and development, cell cycle and photosynthetic functions as well as plant responses to biotic and abiotic stresses [ 5 , 6 , 7 ]. In plants, CATs are encoded by a multigenic family [ 8 ].…”
Section: Introductionmentioning
confidence: 99%